Electronic and magnetic properties of the superhalogen Fe(NO3)3 absorbed monolayer MoS2: The regulating performance. (June 2022) - Zhao, Zi Li; Shao, Peng; Ding, Li-Ping; Zhang, Hui; Tang, Yan; Li, Yi-Wen; Dai, Wei
Abstract: The disadvantages of intrinsic MoS2, such as non-magnetic and single carrier-type, may limit its industrial application. A potential technological approach is to regulate its magnetism and carrier mobility. Here, the functionalization of monolayer MoS2 through adsorption of iron-base magnetic superhalogen Fe(NO3 )3 is systematically studied by using first-principles theory. The results demonstrate that the interaction between Fe(NO3 )3 molecule and monolayer MoS2 is weak. The effect of adsorption on the electronic properties of monolayer MoS2 is analyzed based on electronic band structures, density of states (DOSs) and electron density difference. When Fe(NO3 )3 adsorbs on H-MoS2, the band structures of monolayer H-MoS2 and Fe(NO3 )3 roughly preserve their independence, thus Fe(NO3 )3 can keep its entire magnetic moments. While the adsorption may have a great influence on the electronic properties of T′-MoS2 . Moreover, it is found that the Fe(NO3 )3 adsorption can regulate the mobility of MoS2, especially the electron mobility of H-MoS2 . This study provides a theoretical reference to adjust the electronic properties and magnetism of monolayer MoS2, which may promote its application in electronic devices. Graphical Abstract: The diagram of superhalogen Fe(NO3 )3 absorbed monolayer T′-MoS2 . ga1 Highlights: Fe(NO3 )3 molecule may physically adsorb on both of the H and T′ phase MoS2 . Fe(NO3 )3 adsorption can open a direct band gap of T′-MoS2 . Fe(NO3 )3 adsorption can regulate the mobility of MoS2, especially for H-MoS2 . Magnetic superhalogen can retain its magnetism when it adsorbs on H-MoS2 .